AN ANALYSIS OF PERSUASIVE LANGUAGE FOUND IN SKINCARE INSTAGRAM CAPTIONS - Anisa Nasywa Wahyuni; Semi Sukarni; Abdul Ngafif (Universitas Wiralodra, 2025)
This paper presents the results of a study analyzing the persuasive language found in Instagram captions of four skincare advertisements: Pond’s (@pondsindonesia), Skintific (@skintificid), Somethinc (@somethincofficial), and The Originote (@theoriginote). The types of persuasive language were identified based on Lamb’s theory (2014). Using a descriptive qualitative method, the researcher collected forty data samples from the four skincare brands, with each brand contributing ten Instagram posts. From the forty captions analyzed, the distribution of persuasive language features was as follows: alliteration (1 caption), allusion (4 captions), analogy (2 captions), appeals (3 captions), cliché (1 caption), colloquial language (1 caption), connotation (1 caption), emotive language (3 captions) , evidence (4 captions), hyperbole (2 captions), imagery (1 caption), inclusive language (3 captions), jargon (2 captions), metaphor (3 captions), pun (3 captions), and rhetorical question (6 captions). Among all the persuasive language features identified, rhetorical questions were the most frequently used in skincare advertisements. This highlights the strategic role of rhetorical questions in engaging consumers through Instagram captions. Building on these findings, future research could expand the dataset, compare platforms or product categories, and examine audience responses to evaluate the effectiveness of such strategies.